Assessment of Vitamin D Status, its Determinants and Relationship with Bone Health in Indian Children and Young Adults with Type-1 Diabetes - Shruti Mondkar (Indian Journal of Endocrinology and Metabolism)
Introduction: Recent evidence suggests that vitamin D deficiency and type-1 diabetes (T1D) have a bidirectional cause–effect relationship. The objective of this study is to estimate the prevalence and determinants of vitamin D deficiency in Indian children and young adults with T1D and assess the relationship between vitamin D status and their bone health.